An Analysis of Students’ Errors in Writing Descriptive Text at Tenth Grade of SMAN 1 Tulungagung in Academic Year 2018/2019 - Febriana Surya Dewi; Moh Choirul Huda (STKIP PGRI Tulungagung, 2020)
The students usually make error on the use of grammar when they produce an English writing, also in writing descriptive text. It is due to the difference between Indonesia and English grammatical system. This research aims to find out the types of grammatical errors based on (Caroline Mei Lin Ho, 2005) theory of taxonomy grammatical errors, the most frequently error occurred, and the causes of errors made by the tenth grade students of MIPA 4 at SMAN 1 Tulungagung. The researcher uses qualitative method in order to obtain valid findings from 25 participants of tenth grade students. Based on the error analysis conducted, the researcher found that errors regarding sentence structure are the most dominant errors, with the biggest number of errors are in incomplete or fragmented sentences (36,20%). Then it is followed by errors regarding verb and verb groups with the biggest number of errors are in omission of suffix –s, -es, -ed, and -ing (20,69%). Then, it is followed by errors regarding preposition with the biggest number of errors are in inappropriate selection or usage of preposition (6,03%). Last, the errors regarding noun and noun groups with the biggest number of errors are in inappropriate selection of quantifier, article, determiner (2,58%). The findings show that the students have difficulties in using correct sentence structure, especially in incomplete or fragmented sentences. This problem may occur due to their lack understanding of grammatical rules.